Brazilian translation, cross-cultural adaptation and validation of the MG Composite scale and Quantitative Myasthenia gravis testing form: a multicentric study protocol. - Oliveira, Ezequiel Fernandes de; Urbano, Jessica Julioti; Santos, Israel Reis; Silva, Anderson Soares; Guimarães, Letícia Lopes; Peixoto, Roger André Oliveira; Perez, Eduardo Araújo; Bosio, Paulo Cesar; Polaro, Melissa Nunes; Valério, Berenice Cataldo Oliveira; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Myasthenia gravis (MG) is a chronic and inflammatory disease characterized by progressive weakness of the skeletal muscles due to changes in the synaptic junctions between nerves and muscle fibres. Typically, patients have a history of progressive weakness and fatigue in skeletal muscles, which occurs during sustained or repeated activities and improves after rest. Scoring systems to assess the degree of disease severity are commonly used in clinical drug trials. Further, specific instruments to assess health-related quality of life (HRQOL) have been designed to measure self-perception of symptoms and wellness during the disease or after disease treatment. HRQOL is an important component of patient evaluation, as some individuals can tolerate severe impairment and disability, while others may be very unhappy even with less severe symptom profiles. The objective of the proposed study is to translate and perform a cultural adaptation and validation of two specific instruments for assessing the clinical course of patients with MG. These instruments include the Quantitative Test for Myasthenia gravis (QMG) and Myasthenia gravis Composite Scale (MGC). Methods and analyses: The study design will follow a multi-method approach, and will be conducted in three stages consisting of translation, cultural adaptation, and validation of the QMG and MGC for Brazilian Portuguese patients. This multi-step process will consider aspects of construct and predictive validity as well as reliability and structure of the instrument. The entire process will follow the procedures proposed and developed in other linguistic and social-cultural contexts based on previous studies. Ethics: This study has received approval from the Human Research Ethics Committee of Nove de Julho University (Brazil) under process no. 360.488 based on the Helsinki declaration and is registered with the World Health Organization (WHO) under Universal Trial Number (UTN) U1111-1147-7853 and the Brazilian Registry of Clinical Trials (REBEC) RBR -7ckpdd.